The effectiveness of public subsidies for private innovations: An experimental approach - Julia Brüggemann; Till Proeger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
The effects of public subsidies in supporting innovative activity is subject to long-standing debates. Since empirical findings remain largely inconclusive, this study adds to this debate with counterfactual evidence from a laboratory experiment. In a creative real effort task simulating the innovation process, two distinct means of allocating subsidies are compared to a benchmark treatment without subsidies to identify their effects in fostering innovativeness. Furthermore, subjects' cooperative behavior in relation to subsidies is investigated. Overall, subsidies lead to a substantial crowding-out of private investment. While the individual revenues increase due to the subsidy, the innovative activity fails to increase and less sophisticated innovations are realized. Consequently, subsidies have no or negative effects on overall welfare, depending on the subsidy specifics. However, subsidies do not influence cooperative behavior. These findings imply that the additional costs of subsidies for innovations might not be warranted by gains from additional innovations and increased welfare.
Older version: http://hdl.handle.net/10419/122313
Keywords: C91; H25; O31; 330; creativity; innovation policy; laboratory experiment; real effort task; subsidies